Strong Convergence Bound of the Pareto Index Estimator under Right Censoring. (18th May 2010) - Tao, Bao; Peng, Zuoxiang
Abstract : Let X n, n ≥ 1 be a sequence of positive independent and identically distributed random variables with common Pareto-type distribution functionF ( x ) = 1 − x − 1 / γ l F ( x ) asγ > 0, wherel F ( x ) represents a slowly varying function at infinity. In this note we study the strong convergence bound of a kind of right censored Pareto index estimator under second-order regularly varying conditions.